A checklist for healthcare organisations undergoing transformational change associated with large-scale health information systems implementation. Issue 3 (September 2019) - Sligo, Judith; Roberts, Vaughan; Gauld, Robin; Villa, Luis; Thirlwall, Sarah
Highlights: This article provides evidence from the literature and a real-life example of implementing transformational change. A checklist identifying key factors of transformational change is included. This can be adapted for specific organisations. Effective transformation requires organisational structures, resourcing, workforce requirements and information technology. Abstract: Objectives: Healthcare organisations are increasingly required to undertake transformational change in response to epidemiological and demographic changes, and rapid healthcare technological advances. However, transformational change is notoriously complex and challenging. This article presents a checklist that identifies key components of successful transformational change for organisations planning change. Methods: The checklist was developed after an extensive review of the literature and from the learnings of a realist evaluation of a transformational change process in a New Zealand Healthcare organisation. The article describes the items in the checklist and provides justification from the literature and evaluation. Results: A theoretical framework for the evaluation provided the structure for developing the checklist around four domains: organisational structures, resourcing, workforce, and information technology. These components are foundational: experiences of other organisations show that if these items are not in place or addressed, transformation will not occur. Conclusions: The checklist provides healthcare policy-makers and organisations with a template which can identify each of the components of a complex system. The checklist is created to adapt as organisational transformation evolves so is an advancement in both the use of checklists and in successful implementation of transformational change.